Assessing Land Use, Delay Factors, and Land Pooling Effects in Galchhi, Dhading - Joshi, Trilok; Awasthi, Keshab Datt (Journal of UTEC Engineering Management, 2025)
Land pooling (LP) has emerged as a key tool in Nepal’s urban development strategy, particularly for managing unplanned growth in peri-urban and hilly regions. This study evaluates the Galchhi LP project in Dhading District using GIS analysis and stakeholder-based research to assess three dimensions: discrepancies in land coverage between GIS and cadastral data, causes of project delays, and the overall impact of LP implementation. A mixed-method approach combining spatial mapping, structured questionnaires, and key informant interviews revealed a land area mismatch of 0.77 hectares due to unregistered land use, largely agricultural and residential. Delay factors were analyzed through the Relative Importance Index (RII) and Spearman’s Rank Correlation, identifying top contributors such as political bias, project management turnover, and weak institutional coordination. Despite setbacks, positive outcomes included improved infrastructure and increased land value, although concerns over land contribution ratios and prolonged timelines remain. The study highlights the need for robust institutional frameworks, updated cadastral integration with GIS, and inclusive stakeholder engagement to enhance the effectiveness of LP in Nepal’s urbanizing landscape.